Peran CSR Dalam Mendukung Tujuan Pembangunan Berkelanjutan (SDGS) - Sakina, Laily Hidayah; Assyifa, Zubaidah (EL-EMIR Institute, 2025)
This study aims to explore how the implementation of Corporate Social Responsibility (CSR) can serve as a strategic tool in supporting the achievement of the Sustainable Development Goals (SDGs). A qualitative method was employed using a triangulation approach to analyze data collected through in-depth interviews, direct observation, and document analysis. The findings reveal that CSR programs focusing on education, health, and the environment have a significant impact on achieving SDG targets. Furthermore, CSR acts as a bridge between companies, governments, and communities in collaborative development efforts. However, challenges such as a lack of synergy among stakeholders and weak program monitoring remain major obstacles. This study provides strategic recommendations to enhance the effectiveness of CSR, including strengthening stakeholder collaboration, implementing data-driven evaluation, and aligning programs with national and global development priorities.